1969
DOI: 10.1203/00006450-196911000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Malnutrition: Changes in Body Composition During Rehabilitation

Abstract: ExtractTotal body water (TBW), intracellular (ICW) and extracellular (ECW) spaces, muscle mass and supporting tissue were measured in nine malnourished infants, 5-30 months of age, shortly after, hospitalization, and then following 4-9 months of rehabilitation. Initially all infants had severe growth deficits, height age being 4-64% (average 40 %) and weight age 0-40 % (average 15.6 %) of chronologic age. TBW ranged from 63.5 to 89.3% of body weight and ECW ranged from 38.6 to 50.6% of TBW, suggesting marked l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2

Year Published

1970
1970
1989
1989

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 3 publications
3
29
2
Order By: Relevance
“…4), not observed when these subjects were fed on a surfeit of protein (Nicol & Phillips, 1976b), or in Chilean underprivileged adults fed on a minimum-protein diet (Yanez et al 1982); it has been reported in Indian men (Gopalan & Narasinga Rao, 1966) and in Indian children fed on wheat protein (Reddy, 1971). Adaptation is indicated in these children since there was no response to the lysine supplement in contrast to previous studies (Graham et al 1969). N o explanation for these responses was offered by the authors and, whilst the responses appear rare (they are not observed in Chilean urban poor adults; Yanez et al 1982), there is no reason to question their validity.…”
Section: N O N -R E P R E S E N T a T I V E ' B E H A V I O U R : A Dcontrasting
confidence: 49%
“…4), not observed when these subjects were fed on a surfeit of protein (Nicol & Phillips, 1976b), or in Chilean underprivileged adults fed on a minimum-protein diet (Yanez et al 1982); it has been reported in Indian men (Gopalan & Narasinga Rao, 1966) and in Indian children fed on wheat protein (Reddy, 1971). Adaptation is indicated in these children since there was no response to the lysine supplement in contrast to previous studies (Graham et al 1969). N o explanation for these responses was offered by the authors and, whilst the responses appear rare (they are not observed in Chilean urban poor adults; Yanez et al 1982), there is no reason to question their validity.…”
Section: N O N -R E P R E S E N T a T I V E ' B E H A V I O U R : A Dcontrasting
confidence: 49%
“…Basal G H levels in PEM have been studied extensively (6,(23)(24)(25)(26). There is a general agreement that despite impaired growth rates in children with kwashiorkor, G H concentrations are ele-Measurements of basal insulin levels in children with kwashiorkor have yielded inconsistent results: high (34), low (6,35,36), and normal (37) values have been reported.…”
mentioning
confidence: 96%
“…The fact that all but two had serum albumin levels below 3.0 g/ 100 ml, plus their generally more advanced age, makes them have much in common with most cases of MK. In four cases studied before therapy, we previously found two with "high" fasting levels and two with responses to arginine (14). The evidence suggests that in untreated marasmus, plasma G H is already elevated, or responds appropriately to different stimuli.…”
Section: Normal Infantsmentioning
confidence: 99%
“…Although it was recognized that impaired absorption would influence the results, and that the responses observed might not be maximal, we felt that they would be more representative of responses taking place when such infants are realimented than those to induced hyper-and hypoglycemia or to amino acid infusions (2,4,8,11,12,14,31,39,41). Because of the paucity of reported normal values in infants of different ages, and because control samples handled in the sample manner as the study samples would be more meaningful, we evaluated healthy infants selected to match the study cases in age and body size.…”
Section: Speculationmentioning
confidence: 99%
See 1 more Smart Citation